A Historical Review of the Total Synthesis of Natural Products Developed in Portugal. Issue 17 (25th March 2023) - Clemente, Duarte B.; Coelho, Jaime A. S.
Abstract: Total synthesis of natural products is an important discipline of organic chemistry that has enabled the development of new synthetic methods and strategies for the preparation and study of the structure and reactivity of complex naturally occurring products. In this review we summarize the synthetic strategies developed in Portugal by several research groups for the synthesis of bioactive natural products including alkaloids, cyclitols, fatty alcohols, phenylpropanoic acids, γ‐butyrolactones, xanthones and nucleosides. Abstract : This review summarizes the strategies for the natural product synthesis that were developed in Portugal in the past five decades, including alkaloids, cyclitols, phenylpropanoic acids, γ‐butyrolactones, fatty alcohols, xanthones and nucleosides.